2015
DOI: 10.1063/1.4923061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of thermal convection with temperature- and pressure-dependent viscosity at extreme viscosity contrasts

Abstract: Motivated by convection of planetary mantles, we consider a mathematical model for Rayleigh-Bénard convection in a basally heated layer of a fluid whose viscosity depends strongly on temperature and pressure, defined in an Arrhenius form. The model is solved numerically for extremely large viscosity variations across a unit aspect ratio cell, and steady solutions for temperature, isotherms, and streamlines are obtained. To improve the efficiency of numerical computation, we introduce a modified viscosity law w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that convection is active in the top part of the convecting system (e.g., Christensen, 1984;Fleitout and Yuen, 1984;Christensen, 1985;Stemmer et al, 2006). At high viscosity contrasts the convective system divides to smaller sub-cells (Khaleque et al, 2015;Fowler et al, 2016), which can be interpreted as a reduction in the effective convective depth as we assume in this paper. Thus, it is important to consider pressure-dependent viscosity in the future studies of lithospheric failure.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that convection is active in the top part of the convecting system (e.g., Christensen, 1984;Fleitout and Yuen, 1984;Christensen, 1985;Stemmer et al, 2006). At high viscosity contrasts the convective system divides to smaller sub-cells (Khaleque et al, 2015;Fowler et al, 2016), which can be interpreted as a reduction in the effective convective depth as we assume in this paper. Thus, it is important to consider pressure-dependent viscosity in the future studies of lithospheric failure.…”
Section: Discussionmentioning
confidence: 95%
“…We remark that in this work we analyzed idealized models. This step is just the first of a longer project: further developments should consider rheological aspect of the Earth mantle such as the temperature/pressure viscosity dependence, which still has unsolved numerical issues in 3D domains (Khaleque et al, 2015). Also, analysis of both Newtonian and non Newtonian viscosity has to be considered.…”
Section: Further Tests and Portabilitymentioning
confidence: 99%
“…For these reasons, indirect methods have usually been employed, such as seismic data analysis or numerical simulations. In particular, for the long time-scale behaviour (t τ M ), numerical simulations produce diagnostic and prognostic descriptions of geological processes (Khaleque et al, 2015). Furthermore, because of the high viscosity values (ν = 10 18 − 10 21 m 2 s −1 ), the infinite-Pr number assumption, where Pr = ν κ , ν is the kinematic viscosity and κ the thermal diffusivity, is usually adopted for the Earth mantle (Bercovici, 2007;Turcotte and Schubert, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lenardic et al [9] discussed the depth dependence of viscosity for the mantle. Later dependence of viscosity on both temperature and pressure was examined by Shahraki and Schmeling [10], Khaleque et al [11]. The significant role of viscous dissipation in natural convection in vertical channels has been reported by Ostrach [12] and some others, whereas Gebhart [13] have studied its impact on vertical heated plates.…”
Section: Introductionmentioning
confidence: 98%